2016
DOI: 10.1111/jth.13294
|View full text |Cite
|
Sign up to set email alerts
|

Aging and ABO blood type influence von Willebrand factor and factor VIII levels through interrelated mechanisms

Abstract: To cite this article: Alb anez S, Ogiwara K, Michels A, Hopman W, Grabell J, James P, Lillicrap D. Aging and ABO blood type influence von Willebrand factor and factor VIII levels through interrelated mechanisms. J Thromb Haemost 2016; 14: 953-63. Essentialsvon Willebrand factor (VWF) and factor VIII (FVIII) levels are modulated by age and ABO status. The effect of aging and ABO blood type on VWF and FVIII was assessed in 207 normal individuals. Aging and ABO blood type showed combined and bidirectional influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
121
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 53 publications
(57 reference statements)
15
121
2
1
Order By: Relevance
“…1 and 2), as supported by other studies (Albánez et al, 2016; Favaloro et al, 2005). These may explain the higher incidence of thrombosis in older individuals, since Fbg, FVIII and VWF are the three acknowledged risk factors for thrombosis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…1 and 2), as supported by other studies (Albánez et al, 2016; Favaloro et al, 2005). These may explain the higher incidence of thrombosis in older individuals, since Fbg, FVIII and VWF are the three acknowledged risk factors for thrombosis.…”
Section: Discussionsupporting
confidence: 87%
“…FVIII and VWF levels were significantly lower in O than in non-O groups, whereas no significant differences were calculated among the non-O groups (A, B and AB). Similar results have been confirmed in other populations in USA (Miller et al, 2003), Australia (Favaloro et al, 2005), Norway (Orstavik et al, 1985), Japan (Kokame et al, 2011), Brazil (Rios et al, 2012), Italy (Gallinaro et al, 2008), Canada (Albánez et al, 2016), and so on, which imply that the diversities of FVIII and VWF levels were partially determined by ABO blood types. This result may be explained by the variable clearance of VWF as an effect of the ABO glycosylation patterns.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Albanez S, et al [19] showed the influence of age and the ABO group on the plasma concentration of coagulation factor [19,20]. We were not able to study this point as this parameter was not recorded in our study.…”
Section: Discussioncontrasting
confidence: 47%
“…As a functional assay, VWF ristocetin cofactor (VWF:RCo) levels <30 U/dL are strongly associated with a clinical bleeding phenotype and the presence of an identified VWF mutation in type 1 VWD 12. Other genetic factors that influence VWF levels, including the “platelet type” of VWD18 ( GP1BA mutation) and the ABO blood groups 19. Newer associations between VWF antigen levels and polymorphisms in non-VWF genes have been identified by genome wide association studies, including polymorphisms in secretory protein genes, such as STAB5 , STX2 , and STXBP5 20.…”
Section: The Genetics and Synthesis Of Vwfmentioning
confidence: 99%